2003
DOI: 10.1001/archsurg.138.6.637
|View full text |Cite
|
Sign up to set email alerts
|

Supranormal Trauma Resuscitation Causes More Cases of Abdominal Compartment Syndrome

Abstract: Hypothesis: Normal resuscitation (oxygen delivery index [DO 2 I] Ն500 mL/min per square meter), compared with supranormal trauma resuscitation (DO 2 I Ն600 mL/min per square meter), requires less crystalloid volume, thus decreasing the incidence of intra-abdominal hypertension (IAH) and abdominal compartment syndrome (ACS). Design: Retrospective analysis of a prospective database. Setting: Twenty-bed intensive care unit (ICU) in a regional level I trauma center. Patients: Patients with major trauma (injury sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
210
1
23

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 448 publications
(242 citation statements)
references
References 28 publications
8
210
1
23
Order By: Relevance
“…We enrolled 77 patients (24 women, 53 men) with a mean age of 62.6±16 years (range, 23-97), mean BMI of 24.6±3.9 (range, 18-34) kg/m 2 , mean operation time of 249±109 (range, 35-570) minutes, mean APACHE II score of 9.88±3.25 (range, [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Table 1 shows the distribution of patients according to type of surgery.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We enrolled 77 patients (24 women, 53 men) with a mean age of 62.6±16 years (range, 23-97), mean BMI of 24.6±3.9 (range, 18-34) kg/m 2 , mean operation time of 249±109 (range, 35-570) minutes, mean APACHE II score of 9.88±3.25 (range, [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Table 1 shows the distribution of patients according to type of surgery.…”
Section: Resultsmentioning
confidence: 99%
“…Any enlargement of internal organs due to edema as well as accumulation of ascites/blood or bowel distension increase IAP after abdominal surgery. Visceral edema due to massive fluid infusion is well known in trauma patients (5,7,8). Moreover, in a mixed population critically ill patients Malbrain et al showed that fluid resuscitation >3.5 L was the independent predictor of IAH (2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To avoid infusing excessive amounts of IV solutions and its complications, the condition of responsiveness to volume must be identified [50,[118][119][120]. The filling heart pressures have been used traditionally to accomplish this task, being that the pulmonary artery wedge pressure is considered as the standard.…”
Section: The Hypotense or Hypoperfused Trauma Patient In The Icumentioning
confidence: 99%
“…Estudios recientes han demostrado que balances hídricos positivos persistentes se correlacionan con más intensa disfunción multiorgánica y con peor pronóstico 2,[61][62][63][64][65][66][67] . Esto ha sido demostrado para pacientes críticos en general 63 : sépticos 2,67 , traumatizados 68 , quemados 64 y con síndrome de distress respiratorio agudo 61,62,65 . Así también, balances hídricos positivos se asocian al desarrollo de hipertensión intraabdominal y síndrome compartimental del abdomen 68 .…”
Section: Efectos Deletéreos De La Hiper-reanimaciónunclassified